2009
DOI: 10.1063/1.3208039
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectrum and electromagnetic-field distribution at double-groove metallic surface gratings

Abstract: The Greens function model [8] for calculating the reflection and transmission of light at etched single-groove gratings on both sides of a thin silver film was extended to study the case of double-groove gratings. A splitting of surface-plasmon-polariton (SPP) modes was found due to electromagnetic (EM) coupling between the two grooves in the complex unit-cell of the grating. Spectral features corresponding to the split SPP branches as well as the minigap between them were found in this system. From the full s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In the case of the extraordinary transmission of light through a metal film with a periodic nanoslit array, the surface polaritons supported by the slits play a minor role in the phenomenon, and what is more it is not necessary to have slits that completely pierce the metallic film to achieve the enhanced transmission 4 . When a periodic nanogroove array is illuminated by p−polarized light, whose magnetic vector is parallel to the generators of the array, surface plasmon polaritons (SPPs) associated with the film-cladding and the film-substrate interfaces are excited 4,5 , and are diffracted by the structure into transmitted volume waves in the substrate. The periodicity of the array enhances the excitation of surface plasmon polaritons associated with the cladding-film interface and the conversion of surface plasmon polaritons associated with the substrate-film interface into volume waves in a range of SPP frequencies whose wavenumbers are in the vicinity of the boundary of the second Brillouin zone, i.e.…”
Section: Kimmentioning
confidence: 99%
“…In the case of the extraordinary transmission of light through a metal film with a periodic nanoslit array, the surface polaritons supported by the slits play a minor role in the phenomenon, and what is more it is not necessary to have slits that completely pierce the metallic film to achieve the enhanced transmission 4 . When a periodic nanogroove array is illuminated by p−polarized light, whose magnetic vector is parallel to the generators of the array, surface plasmon polaritons (SPPs) associated with the film-cladding and the film-substrate interfaces are excited 4,5 , and are diffracted by the structure into transmitted volume waves in the substrate. The periodicity of the array enhances the excitation of surface plasmon polaritons associated with the cladding-film interface and the conversion of surface plasmon polaritons associated with the substrate-film interface into volume waves in a range of SPP frequencies whose wavenumbers are in the vicinity of the boundary of the second Brillouin zone, i.e.…”
Section: Kimmentioning
confidence: 99%
“…If η L = η R = 0 for a PEC, we can explicitly express 22 the continuous Fourier expansion coefficients A s (β), A a (β), B s (β) and B a (β) by the discrete Fourier expansion coefficients a j sn , b j sn , a j an and b j an through Eqs. (13), (14), (15) and (16). If there exists only one slit (j = 0 and z 0 = 0), the PEC single slit does not couple symmetric modes to anti-symmetric ones 25 .…”
Section: This Leads Tomentioning
confidence: 99%
“…It could lead to strong field enhancement in nanoscale and this makes the spectrum extremely sensitive to the physical properties of the environment [7]. Previous studies showed that SPPs could lead to the enhanced reflection and DR near the resonance frequency [14][15][16]. Taking advantage of SPPs offers a potential approach to significantly enhance the sensitivity of the DR technique and extend the applications of this technique.…”
Section: Introductionmentioning
confidence: 97%